1989
DOI: 10.1111/j.1600-0404.1989.tb01808.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of pentoxifylline vs antiaggregants in patients with transient ischaemic attacks

Abstract: Out of 235 patients with recent cerebral transient ischaemic attacks, 208 subjects were available for final evaluation after 6 months' randomised treatment with either pentoxifylline (PTX 1200 mg/day) or a combination (ASAD) of acetylsalicylic acid (ASA, 1050 mg/day) and dipyridamole (D, 150 mglday). Prevention of TIA, stroke or death attributable to previous events were endpoint criteria.The pentoxifylline group (n = 100) exhibited no recurrent episodes in 86 patients (86010). TIA occurred in 9 patients, stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…A subsequent larger study by the same group, likewise of 6-month duration, observed recurrent TIAs in 14% of patients receiving pentoxifylline, and 24.1% of those receiving aspirin/dipyridamole. 48 Treatment of acute ischaemic stroke Four controlled trials, enrolling a total of 763 patients, have assessed the impact of intravenous pentoxifylline on early mortality following acute ischaemic stroke. The daily doses employed ranged from 600 to 1200 mg, and were administered for 3-5 days immediately following stroke onset; in the three studies in which intravenous pentoxifylline was given for 3 days, this was followed up with oral pentoxifylline.…”
Section: Prevention Of Stroke and Transient Ischaemic Attacksmentioning
confidence: 99%
“…A subsequent larger study by the same group, likewise of 6-month duration, observed recurrent TIAs in 14% of patients receiving pentoxifylline, and 24.1% of those receiving aspirin/dipyridamole. 48 Treatment of acute ischaemic stroke Four controlled trials, enrolling a total of 763 patients, have assessed the impact of intravenous pentoxifylline on early mortality following acute ischaemic stroke. The daily doses employed ranged from 600 to 1200 mg, and were administered for 3-5 days immediately following stroke onset; in the three studies in which intravenous pentoxifylline was given for 3 days, this was followed up with oral pentoxifylline.…”
Section: Prevention Of Stroke and Transient Ischaemic Attacksmentioning
confidence: 99%
“…Experimental works show that oral administration of PTF (40 mg/kg) to rabbits fed with a cholesterolenriched diet to induce atherosclerotic plaque was found to decrease the area of aortic atherosclerotic plaque by 38% without changes in serum lipids [23]. In the clinical scenario, two 6-month RCTs evaluated the effects of PTF in patients experiencing transient ischemic attacks (TIAs) compared with a control group receiving asprin + dipyridamole [24,25]. During the follow-up, proportion of recurrent TIAs was 14% in the PTF group, and 24.1% in the group receiving aspirin/dipyridamole.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four strokes occurred in the aspirin/dipyridamole group compared with two in the Px group [ 42 ]. A subsequent larger randomized study over 6 months showed that recurrent TIAs occurred in 9% with Px and 20% with aspirin/dipyridamole, and the composite of TIA, strokes and death occurred in 14% on Px and 24.1% with aspirin/dipyridamole [ 43 ].…”
Section: Cerebrovascular Diseasementioning
confidence: 99%